Morfologi Serangga Yang Tertarik Pada Perangkap Warna di Perkebunan Cabai Merah Desa Pedu Kecamatan Jejawi Kabupaten OKI - Mustakim, Hazal; Mutiara, Dian; Rosanti, Dewi (Universitas PGRI Palembang, 2024)
Research on the morphology of insects attracted to color traps was carried out in April-June 2023, aiming to study the interest of insects to color and their morphology in red chili plantations, Pedu Village, Jejawi Sub-district, OKI District. This study used a survey method. Sampling by purposive sampling. The color traps used are red, yellow, green and blue. The observation parameter is the number of trapped insect species. Many insects are housed both in the number of species and in the number of individuals of each species. The results of the study found 11 insect species namely, Bactrocera dorsalis, Epilachna sp, Periplanetta americana, Bemisia tabaci, Nezara viridula, Valanga nigriconis, Odontomachus sp., Musca domestica, Agelastica alni, Oxya chinensis, Polistes sp. scattered in red 8 species, yellow 8 species, green 8 species, and blue 1 species. Mouth morphology types include chewing, sucking, piercing-sucking, biting-sucking, and biting-chewing. Head morphology types include hypognathus, prognathus, and opistrorincus types. Antenna morphology types include filiform, clavate, pectinate, aristale, and geniculate types. Wing morphology types include membrane, elytra, halter, and tegmina types. The morphological types of insect violations include cursorial, saltatorial, raptatorial, and natatorial types. 81% of pests, 9% of saprophagus and 9% of pollinators get the role of insects.